Peningkatan Kemampuan Menggunakan Huruf Kapital melalui Metode Penugasan pada siswa Kelas V SDN Inti Tondo Palu - Ulfah Ulfah (Jurnal Dikdas, 2015)
The problem in this research was whether the application of assignment method can improve the fifth grade students’ ability using the capital letters at SDN Inti Tondo Palu? The study aimed to  improve the fifth grade students’ ability using the capital letters  through  the  assignment  method   at   SDN  Inti  Tondo  Palu.  The  researh methodology used a descriptive method by applying the  class action research with phases of planning, action, observation and reflection. The data collection  technique was  conducted  by  using  observation  and  evaluation,  while  data  analysis  method through formulation of the classical and individual completeness as well as determine the students’ average score in each cycle. The results showed the average score of 6,07 was obtained in the first cycle and the average score of 9 was obtained in the second cycle. As a result the research was considered succeeded.